Intraoperative Sentinel Events in the Era of Surgical Safety Checklists: Results of a National Survey. Issue 4 (December 2020) - Cramer, John D.; Balakrishnan, Karthik; Roy, Soham; David Chang, C. W.; Boss, Emily F.; Brereton, Jean M.; Monjur, Taskin M.; Nussenbaum, Brian; Brenner, Michael J.
Objective: Despite the implementation of advanced health care safety systems including checklists, preventable perioperative sentinel events continue to occur and cause patient harm, disability, and death. We report on findings relating to otolaryngology practices with surgical safety checklists, the scope of intraoperative sentinel events, and institutional and personal response to these events. Study Design: Survey study. Setting: Anonymous online survey of otolaryngologists. Methods: Members of the American Academy of Otolaryngology–Head and Neck Surgery were asked about intraoperative sentinel events, surgical safety checklist practices, fire safety, and the response to patient safety events. Results: In total, 543 otolaryngologists responded to the survey (response rate 4.9% = 543/11, 188). The use of surgical safety checklists was reported by 511 (98.6%) respondents. At least 1 patient safety event in the past 10 years was reported by 131 (25.2%) respondents; medication errors were the most commonly reported (66 [12.7%] respondents). Wrong site/patient/procedure events were reported by 38 (7.3%) respondents, retained surgical items by 33 (6.4%), and operating room fire by 18 (3.5%). Although 414 (79.9%) respondents felt that time-outs before the case have been the single most impactful checklist component to prevent serious patient safety events, several respondents also voiced frustrations with the administrative burden. Conclusion: Surgical safety checklists are widely used in otolaryngology and are generally acknowledged as the most effective intervention to reduce patient safety events; nonetheless, intraoperative sentinel events do continue to occur. Understanding the scope, causes, and response to these events may help to prioritize resources to guide quality improvement initiatives in surgical safety practices.